The Use of Video Media Against Adolescent Knowledge Level of Breast Self Examination (BSE) - Anggriani, Yunita; Rahayu, Sri; Sukarni, Sukarni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Breast cancer is one of the diseases that contribute to the highest mortality rate in Indonesia. The low knowledge of young women about BSE examinations is one thing that affects the high cases of breast cancer. Counseling using video media can be an alternative to increase the knowledge of adolescents about BSE examinations. The purpose of the study was to know the effect of counseling using video media on the level of knowledge related to BSE examinations in adolescent girls at SMK HMPTI Tulang Bawang. This type of quantitative research with a quasi-experimental design uses a one-group pretest-posttest approach. The population is all students of class X SMK HMPTI Tulang Bawang, the sample used is 28 students with a sampling technique using purposive sampling. The analysis used is the paired t-test. The results of the analysis obtained knowledge of students before counseling BSE 9.04, after being given counseling 11.14. Then obtained a p-value of 0.001 which means that there is an effect of health education on BSE on increasing students' knowledge. It is hoped that the results of the study can be used as information material to increase knowledge so that young women can carry out BSE examinations correctly. Abstrak: Kanker payudara menjadi salah satu penyakit yang menyumbang angka kematian terbanyak di Indonesia. Rendahnya pengetahuan remaja putri mengenai pemeriksaan SADARI menjadi satu hal yang mempengaruhi tingginya kasus kanker payudara. Penyuluhan menggunakan media video dapat menjadi alternatif untuk meningkatkan pengetahuan remaja putri mengenai pemeriksaan SADARI. Tujuan penelitian diketahui pengaruh penyuluhan menggunakan media video terhadap tingkat  pengetahuanterkait pemeriksaan SADARI pada remaja putri di SMK HMPTI Tulang Bawang. Jenis penelitian kuantitatif dengan design quasi eksperimen menggunakan pendekatan one group pretest postest. Populasinya adalah seluruh siswi kelas X SMK HMPTI Tulang Bawang, sampel yang digunakan 28 siswi dengan tehnik pengambilan sampel menggunakan purposive sampling. Analisis yang digunakan adalah uji paired t-test. Hasil analisis didapatkan pengetahuan siswi sebelum penyuluhan SADARI 9.04,sesudah diberikan penyuluhan 11.14. Kemudian didapatkan p-value 0,001 yang berarti adanya pengaruh penyuluhan kesehatan tentang SADARI terhadap peningkatan pengetahuan siswi.Diharapkan hasil penelitian dapat digunakan sebagai bahan informasi untuk menambah pengetahuan sehingga remaja putri dapat melakukan pemeriksaan SADARI dengan benar.